Government policy on health worker competency testing regulations - Hastuti, Puji; Wahyuningrat, Wahyuningrat (International Journal on Social Science, Economics and Art, 2025)
The health worker competency test is an Indonesian government policy aimed at ensuring that health workers, such as doctors, nurses, midwives, and other medical personnel, have adequate competency and professional standards before officially working. The competency test is a process of measuring the knowledge, skills, and attitudes of students at universities that provide higher education in the health sector. The implementation of the competency test itself has experienced various problems and changes. For example, the competency test for graduates of health universities is considered not in accordance with the mandate of the Higher Education Law and the Health Worker Regulation because it is carried out by a national committee. The Purwokerto Midwifery Study Program, Diploma Three Program, is a health worker institution that graduates midwives and has conducted competency tests for its graduates. The purpose of this study is to describe the pass rate of the competency test since participating in 2020 to 2024 for 5 years at the Purwokerto Midwifery Study Program, Diploma Three Program, and the preparations made for the competency test as well as the obstacles experienced in implementing the competency test. The research method uses secondary data derived from educational reports to describe the pass rate of the competency test. Interviews and observations to examine the preparation and obstacles in implementing the competency test. From the 2020 to 2024 competency tests, graduates were declared 100% competent. One retaker in 2022 was declared competent at the next stage. Preparation for the competency test included identifying students who met the requirements and providing refreshers on the test questions. A perceived obstacle was server inefficiency during the exam. Students were advised to prepare well for the test to be declared competent.